Involvement of opioid system, TRPM8, and ASIC receptors in antinociceptive effect of Arrabidaea brachypoda (DC) bureau - Rodrigues, Vinícius Peixoto [UNESP]; Da Rocha, Cláudia Quintino; Périco, Larissa Lucena [UNESP]; De Cássia dos Santos, Raquel; Ohara, Rie [UNESP]; Nishijima, Catarine Massucato [UNESP]; Queiroz, Emerson Ferreira; Wolfender, Jean-Luc; Da Rocha, Lúcia Regina Machado [UNESP]; Santos, Adair Roberto Soares; Vilegas, Wagner [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP] (MDPI, 2017)
Arrabidaea brachypoda (DC) Bureau is a medicinal plant found in Brazil. Known as “ció-una”, it is popularly used as a natural therapeutic agent against pain and inflammation. This study evaluated the chemical composition and antinociceptive activity of the dichloromethane fraction from the roots of A. brachypoda (DEAB) and its mechanism of action. The chemical composition was characterized by high-performance liquid chromatography, and this fraction is composed only of dimeric flavonoids. The antinociceptive effect was evaluated in formalin and hot plate tests after oral administration (10-100 mg/kg) in male Swiss mice. We also investigated the involvement of TRPV1 (transient receptor potential vanilloid 1), TRPA1 (transient receptor potential ankyrin 1), TRPM8 (transient receptor potential melastatin 8), and ASIC (acid-sensing ion channel), as well as the opioidergic, glutamatergic, and supraspinal pathways. Moreover, the nociceptive response was reduced (30 mg/kg) in the early and late phase of the formalin test. DEAB activity appears to involve the opioid system, TRPM8, and ASIC receptors, clearly showing that the DEAB alleviates acute pain in mice and suggesting the involvement of the TRPM8 and ASIC receptors and the opioid system in acute pain relief.
Keywords: Antinociceptive effect; Arrabidaea brachypoda (dc) bureau; Bignoniaceae; Pain